PJBL Terintegrasi Stem Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa Kelas XII SMA - Sholicatul Amin; Mar’atus Sholihah (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The 21st century is an era where knowledge is easily spread and technology is developing rapidly. The close relationship between science and technology allows for accelerated synergy. This study aims to determine the effect of the Project Based Learning model based on Science, Technology, Engineering, Mathematic. In the subject of Biology on the ability to think critically and creatively in class XII high school students. This study used a Quasi Experiment with research subjects in class XII IPA SMAN 1 Kademangan. The sample used was 34 students as the control class and 34 students as the experimental class. The data analysis technique used is the prerequisite test for normality and homogeneity and the ANACOVA hypothesis test. The results show that there is an increase in critical thinking skills and in the experimental class of 72,6%. In addition, there are differences in the abiliy to think creatively in student who used STEM integrated PJBL. PJBL terintegrasi STEM Meningkatkan Kemampuan Berpikir Kritis dan Kreatif Siswa Kelas XII SMA